2016
DOI: 10.1016/j.pan.2016.06.118
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of resection rates and clinical outcomes after FOLFIRINOX-based treatment in patients with locally advanced pancreatic cancer

Abstract: Background. FOLFIRINOX prolongs survival in patients with metastatic pancreatic cancer and may also benefit patients with locally advanced pancreatic cancer (LAPC). Furthermore, it may downstage a proportion of LAPC into (borderline) resectable disease, however data are lacking. This review assessed outcomes after FOLFIRINOX-based therapy in LAPC. Methods. The PubMed, EMBASE and Cochrane library databases were systematically searched for studies published to 31 August 2015. Primary outcome was the (R0) resecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 1 publication
2
21
1
Order By: Relevance
“…One meta‐analysis found 43% of patients with borderline resectable and locally advanced disease were able to be resected after preoperative FOLFIRINOX with or without radiation, with a complete resection (R0) rate of 85% . Similarly, another systematic review of locally advanced pancreatic cancer patients found that 28% underwent resection after FOLFIRINOX with or without radiation, with a 77% R0 resection rate . Consistent with these prior studies, this study demonstrated that patients treated with neoadjuvant therapy had smaller tumors and fewer nodes positive on pathologic staging compared to patients treated with surgery first (see Table ), supporting the idea that neoadjuvant therapy results in downstaging of the tumor.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…One meta‐analysis found 43% of patients with borderline resectable and locally advanced disease were able to be resected after preoperative FOLFIRINOX with or without radiation, with a complete resection (R0) rate of 85% . Similarly, another systematic review of locally advanced pancreatic cancer patients found that 28% underwent resection after FOLFIRINOX with or without radiation, with a 77% R0 resection rate . Consistent with these prior studies, this study demonstrated that patients treated with neoadjuvant therapy had smaller tumors and fewer nodes positive on pathologic staging compared to patients treated with surgery first (see Table ), supporting the idea that neoadjuvant therapy results in downstaging of the tumor.…”
Section: Discussionsupporting
confidence: 74%
“…Neoadjuvant therapy is increasingly being utilized in borderline resectable and locally advanced pancreatic cancer to improve margin negative resection rates or increase resectability, particularly in high‐volume and academic centers . One meta‐analysis found 43% of patients with borderline resectable and locally advanced disease were able to be resected after preoperative FOLFIRINOX with or without radiation, with a complete resection (R0) rate of 85% .…”
Section: Discussionmentioning
confidence: 99%
“…The evidence for platinum therapy in PDAC is ever increasing in the neoadjuvant, adjuvant and palliative settings (42)(43)(44)(45)(46)(47). Exceptional responders to platinum therapy are well documented, yet biomarkers of response require testing in prospective clinical trials (9,39).…”
Section: Targeting Ddr Deficiencymentioning
confidence: 99%
“…[15] Despite the improvement of survival rates after the advent of FOLFIRINOX, a combination chemotherapy, LAPC still has a poor prognosis. [6]Therefore, local ablative techniques are being explored as a new treatment options for LAPC, in the hope of substantial survival benefit. [7]…”
Section: Introductionmentioning
confidence: 99%